Pengaruh Perceived Value dan Perceived Quality Terhadap Kepuasan Pengunjung Domestik di Saung Angklung Udjo - Ahmad Riyadi; Suryanto Suryanto; Ratih Purbasari (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to explain and examine the effect of perceived value and perceived quality on the satisfaction of domestic visitors at Saung Angklung Udjo. The study employs a quantitative approach with an explanatory research design, focusing on testing the causal relationships among variables. Data were collected through a survey using structured questionnaires with a Likert scale administered to 97 respondents, selected through non-probability sampling using a purposive sampling technique. The data were analyzed using multiple linear regression analysis, preceded by validity and reliability tests as well as classical assumption tests, and followed by partial hypothesis testing (t-test) and simultaneous hypothesis testing (F-test). The results indicate that perceived value and perceived quality have a positive and significant effect on visitor satisfaction, both partially and simultaneously. Perceived value is found to have a more dominant influence than perceived quality, indicating that the value of the interactive and educational cultural experience provided through the main performance is a stronger factor in shaping visitor satisfaction. These findings confirm that, within the context of interactive cultural performance tourism, visitor satisfaction is formed through a combination of the value and benefits received from the performances with the service and facility quality experienced during the visit.